Hyponatraemia in patients with community‐acquired pneumonia; prevalence and aetiology, and natural history of SIAD. (18th March 2019) - Cuesta, Martin; Slattery, David; Goulden, Eirena L.; Gupta, Saket; Tatro, Elizabeth; Sherlock, Mark; Tormey, William; O'Neill, Shane; Thompson, Christopher J.
Summary: Objective: Hyponatraemia is common in community‐acquired pneumonia (CAP) and is associated with increased mortality. The mechanism of hyponatraemia in CAP is not completely understood and treatment is therefore ill‐defined. We aimed to define the causation of hyponatraemia in CAP. Design: Prospective, single‐centre, observational study of all patients with CAP and hyponatraemia (≤ 130 mmol/L) during a 9‐month period. Patients: The prevalence of each subtype of hyponatraemia, and the associated mortality, was determined in 143 admissions with CAP (Study 1). A sub‐cohort of patients with SIAD (n = 10) was prospectively followed, to document the natural history of SIAD associated with CAP (Study 2). Measurements: In Study 2, blood and urine were collected on day 1, 3, 5 and 7 following admission for measurement of plasma vasopressin, sodium, osmolality and urine osmolality. Results: In study 1, 143/1723(8.3%) of CAP patients had hyponatraemia (≤130 mmol/L). About 66 had SIAD (46%), 60(42%) had hypovolaemic hyponatraemia (HON), 13(9%) had hypervolaemic hyponatraemia (HEN) and 4(3%) patients had hyponatraemia due to glucocorticoid hormone deficiency. Mortality was higher in the HEN than in the HON, SIAD or normonatraemic groups ( P  < 0.01). In Study 2, plasma sodium concentration normalized in 8/10 (80%) by day 7. Two patients with persistent hyponatraemia were discovered to have underlying bronchiectasis. Conclusions: Hyponatraemia in CAP is most commonly secondary to SIAD or hypovolaemia. HEN is less common, but has worse prognosis. Prospective observation demonstrates that in SIAD, plasma AVP and sodium concentrations normalize with antimicrobials; failure of reversal of suggests underlying lung disease, such as bronchiectasis.